2010
DOI: 10.1111/j.1399-0012.2010.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transplant lymphoproliferative disorders in lung transplant recipients: 20‐yr experience at the University of Minnesota

Abstract: Post-transplant lymphoproliferative disorders (PTLD) are potentially fatal complications of solid organ transplantation. The natural history of PTLD varies considerably among the different types of organs transplanted. While lung transplant recipients are highly susceptible to PTLD, there are only a few small studies that detail PTLD in this setting. We undertook this study to better describe the characteristics and treatment response in PTLD after lung transplantation. We conducted a retrospective chart revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…We confirm the low incidence of PTLD in our experience, but in recent years, we have also encountered some late-occurring cases. Several series have shown that such PTLD cases occurring late after transplantation (usually after 1 year) were different from early cases [4,5,7,11]. Indeed, in our series, the 5 cases occurring more than 4 years after transplantation contrasted with the 11 cases occurring less than 18 months after transplantation.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…We confirm the low incidence of PTLD in our experience, but in recent years, we have also encountered some late-occurring cases. Several series have shown that such PTLD cases occurring late after transplantation (usually after 1 year) were different from early cases [4,5,7,11]. Indeed, in our series, the 5 cases occurring more than 4 years after transplantation contrasted with the 11 cases occurring less than 18 months after transplantation.…”
Section: Discussioncontrasting
confidence: 52%
“…These rare lesions are called posttransplant lymphoproliferative disorders (PTLD), and most are Epstein-Barr virus (EBV) related. PTLD in the setting of lung transplantation has some specificities: a higher incidence as compared with transplantation of most other organs [1,3], a frequent involvement of the grafted lung [3,4,5,6], and the risk of dysfunction or loss of a vital graft if immunosuppression is importantly reduced [4,7]. PTLD mostly occur in the first posttransplant year [8], but late cases have been increasingly reported in lung transplant recipients [4,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these LPDs occur as a consequence of Epstein-Barr virus (EBV) infection after solid organ transplant or HSCT, and are appropriately named posttransplant lymphoproliferative disorders (PTLDs). [204,205] Children can also develop viralLPDs with inherited immune deficiencies, including, but not limited to, ataxia telangiectasia, Wiscott-Aldrich syndrome, severe combined immune deficiency, and common variable immunodeficiency. [206,207] PTLDs and other viral-LPDs have the potential for malignant transformation and can be life threatening.…”
Section: Lymphoproliferative Disordersmentioning
confidence: 99%
“…Generally, immunosuppression post lung transplantation consists of a higher degree of immunosuppression than that used for other organs, therefore a higher incidence of PTLD is seen in lung transplant recipients. [4][5][6] PTLD in solid organ transplantation is almost always identified in recipients. When it is identified, it most often occurs within the first year after transplantation, although PTLD after allo-HSCT is predominantly derived from donor B cells and typically occurs within the first 6 months after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 To date, however, HHV6-associated pleurisy has not been recognized as a complication of HSCT. In this report, we describe an adult HSCT recipient who developed HHV6-associated pleurisy after an unrelated cord blood transplantation (CBT).…”
Section: Introductionmentioning
confidence: 99%